An observational study of trait and state fatigue, and their relation to cognitive fatigability and saccade performance - Marika C Möller; Jan Johansson; Giedre Matuseviciene; Tony Pansell; Catharina Nygren Deboussard (Concussion)
Aim: Different fatigue measurements and their relation to saccadic functions were investigated in 15 patients with a mild traumatic brain injury (mTBI) and 15 orthopedic controls. Materials & metho...